Implementasi Undang-undang Perkawinan No. 1 Tahun 1974 dalam Pemberian Dekke Simudur Udur Erat pada Masyarat Batak Toba - Roswita Sitompul (JURNAL MERCATORIA, 2020)
Marriage is away for humans to developing off spring, there fore important thing is that marriage is regulated by the state, religion and customs. In Batak custom marriageis legal if it is done according toreligionthen the marriageis considered invalid, and peoplewho do marriage like this may not take partin any traditional ceremonies. This reseach is an exploratory study using primer and secondary data, the data collection is done by interviews, questionnaries andobservations the data coollectedis evaluatedqualitativelyand quantitatively so based on theabove datait canbe concluded that the batak toba people in Medan still do traditional marriage such giving “dekke si mudur udur” give to hula- hula. Hula-hula will give good words of blesssingor advise for the bride’s life in the future.